JEWISH WORD SPECIAL EDITION. (Moment Magazine)
The article focuses on favorite Jewish words and 1972 entry in the Oxford English Dictionary, where the earliest citation of the word dated back to astronaut John Glenn's 1962 account of Project Mercury. It mentions Yale law librarian named Fred Shapiro dates the first printed record of glitch's radio pedigree to a 1940 syndicated newspaper column by novelist Katharine Brush. It also mentions ubiquity of crashing computers and freezing smartphone screens.